Intraoral anastomosis in maxillary microvascular reconstruction after oncological excision. Issue 9 (September 2021) - Bueno de Vicente, A.; Almeida, F.; Nuñez, J.A.; Picon, M.; Acero, J.
Abstract: Microvascular anastomosis using an intraoral approach can avoid unnecessary external incisions thus improving patient satisfaction. Furthermore, in case of short pedicle flaps, the lack of proximity of the recipient vessels can be a problem in microvascular reconstruction of the midface. We present our experience in six patients treated for tumours affecting the midface and reconstructed with microvascular flaps through anastomosis to the intraoral aspect of the facial vessels, with the aim of reviewing the use of this technique. Our results showed that intraoral anastomosis is a feasible technique that can be used in the reconstruction after tumours resection, avoiding additional external incisions in patients with no previous cervicotomy incisions. In two cases, a vein graft was interposed to perform the intraoral arterial anastomosis in a tension-free situation without increasing morbidity. The technical features and advantages of intraoral anastomosis were reviewed.